Chimpanzee vertebrate consumption: Savanna and forest chimpanzees compared. Issue 112 (November 2017) - Moore, Jim; Black, Jessica; Hernandez-Aguilar, R. Adriana; Idani, Gen'ichi; Piel, Alex; Stewart, Fiona
Abstract: There is broad consensus among paleoanthropologists that meat-eating played a key role in the evolution of Homo, but the details of where, when, and why are hotly debated. It has been argued that increased faunivory was causally connected with hominin adaptation to open, savanna habitats. If savanna-dwelling chimpanzees eat meat more frequently than do forest chimpanzees, it would support the notion that open, dry, seasonal habitats promote hunting or scavenging by hominoids. Here we present observational and fecal analysis data on vertebrate consumption from several localities within the dry, open Ugalla region of Tanzania. Combining these with published fecal analyses, we summarize chimpanzee vertebrate consumption rates, showing quantitatively that savanna chimpanzee populations do not differ significantly from forest populations. Compared with forest populations, savanna chimpanzees consume smaller vertebrates that are less likely to be shared, and they do so more seasonally. Analyses of chimpanzee hunting that focus exclusively on capture of forest monkeys are thus difficult to apply to chimpanzee faunivory in open-country habitats and may be misleading when used to model early hominin behavior. These findings bear on discussions of why chimpanzees hunt and suggest that increases in hominin faunivory were related to differences between hominins and chimpanzees and/or differences between modern and Pliocene savanna woodland environments.